Copper particle catalyst electrode containing abundant dislocation defects as well as preparation method and application of copper particle catalyst electrode
By preparing copper particle catalyst electrodes with rich dislocation defects, the problem of nitrite accumulation in the process of electrocatalytic reduction of nitrate ammonia is solved, and the effect of improving the reaction rate and ammonia nitrogen selectivity is achieved.
Patent Information
- Application Number
- CN202510049612.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
AI Technical Summary
During the process of electrocatalytic reduction of nitrate ammonia, the copper-based catalyst has weak binding to nitrogen intermediates, resulting in accumulation of nitrite, affecting the selectivity of ammonia nitrogen.
By preparing copper particles catalyst electrodes rich in dislocation defects, CuWO4 precursors are prepared by hydrothermal method, and copper particles catalysts are formed through electrochemical reduction processes to enhance their adsorption ability to nitrogen intermediates.
The reaction rate of electrocatalytic reduction of nitrate is improved, the accumulation of nitrite is reduced, and the selectivity and catalytic activity of ammonia nitrogen is improved.
Smart Images

Figure CN119843308A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a copper particle catalyst electrode rich in dislocation defects and a preparation method and application thereof. Background Art
[0002] Ammonia is a basic chemical raw material that is vital to human production activities. The traditional ammonia production process mainly uses the Haber process, which is an energy and carbon intensive industry, accounting for about 2% of global energy consumption and 1% of carbon dioxide emissions. Recently, the electrocatalytic reduction of nitrate has been widely used in the ammonia industry. Due to the high solubility and low dissociation energy of nitrate, the electrocatalytic reduction of nitrate to synthesize ammonia has a high reaction rate and energy efficiency. At the same time, since nitrate is a common pollutant in industrial wastewater and surface water, this route also has great application prospects in nitrate pollution remediation and nitrogen source recovery.
[0003] The catalyst material in the electrocatalytic reduction of nitrate to ammonia process is the focus of research. Copper-based catalysts are widely used due to their abundant earth reserves and the low overpotential required in the process of converting nitrate to nitrite. However, copper-based catalysts will cause nitrite accumulation due to their weak binding with nitrogen intermediates. Therefore, modifying copper-based catalysts, accelerating the reaction rate, reducing the desorption of nitrite and other nitrogen intermediates in the reaction, and improving ammonia nitrogen selectivity are the current research focuses in this field. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a copper particle catalyst electrode rich in dislocation defects and its preparation method and application, wherein the defect sites can enhance the adsorption of nitrogen intermediates, increase the reaction rate, reduce the accumulation of nitrite, and enhance the activity of electrocatalytic reduction of nitrate and the selectivity of ammonia nitrogen.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention discloses a method for preparing a copper particle catalyst electrode containing abundant dislocation defects, comprising the following steps:
[0007] (1) Dissolve tungstate, copper salt and urea in water and stir to mix;
[0008] (2) placing the solution formed in step (1) into a hydrothermal kettle for hydrothermal reaction, and then washing and drying the solid powder obtained by the reaction;
[0009] (3) calcining the solid powder obtained in step (2) in air to obtain CuWO4 powder;
[0010] (4) loading the CuWO4 powder obtained in step (3) on an electrode substrate to prepare a working electrode;
[0011] (5) electrochemically reducing the working electrode obtained in step (4) to obtain a copper particle catalyst electrode rich in dislocation defects.
[0012] As a preferred technical solution, in step (1), the tungstate is one or more of Na2WO4·2H2O and K2WO4·2H2O; the copper salt is one or more of CuCl2, CuSO4 and Cu(NO3)2.
[0013] As a preferred technical solution, in step (1), the molar ratio of tungstate, copper salt and urea is 1:1.05:10-20.
[0014] As a preferred technical solution, in step (2), the hydrothermal reaction temperature is 160°C to 200°C, and the reaction time is 8 to 16 hours.
[0015] As a preferred technical solution, in the step (3), the calcination temperature is 300° C. to 500° C., and the calcination time is 2 to 12 hours.
[0016] As a preferred technical solution, in step (5), the voltage of electrochemical reduction is -1.3V to -1.5V, the reference electrode is an Ag / AgCl electrode, and the counter electrode is a Pt electrode.
[0017] The invention also discloses a copper particle catalyst electrode rich in dislocation defects, which is prepared by the preparation method.
[0018] The invention also discloses the application of the copper particle catalyst electrode containing abundant dislocation defects in the electrocatalytic reduction of nitrate.
[0019] As a preferred technical solution, the reaction voltage of the electrocatalytic reduction of nitrate is -1.0 to -1.1V.
[0020] The beneficial effects of the present invention are:
[0021] The present invention uses a CuWO4 precursor prepared by a hydrothermal method, which is coated on an electrode to prepare a working electrode, and a reduction voltage is applied to activate the CuWO4. 2+ Reduction to Cu 0 , while WO4 2- The ions dissolve into the solution, forming a copper particle catalyst electrode rich in dislocation defects. The defect sites of this electrode can regulate the electronic structure of copper, construct low-coordinated copper, enhance the binding ability to nitrogen intermediates, thereby reducing nitrite accumulation and improving reaction activity and ammonia nitrogen selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0023] Figure 1 The XRD pattern of the copper particle catalyst electrode rich in dislocation defects prepared in Example 1;
[0024] Figure 2 TEM image of the copper particle catalyst electrode rich in dislocation defects prepared in Example 1;
[0025] Figure 3 This is a reverse Fourier transform image of the copper particle catalyst electrode containing abundant dislocation defects prepared in Example 1;
[0026] Figure 4 This is a graph showing the change in nitrogen species concentration over time in the electrocatalytic reduction of nitrate by the copper particle catalyst electrode rich in dislocation defects prepared in Example 1;
[0027] Figure 5 This is a stability test diagram of the continuous flow reaction of electrocatalytic reduction of nitrate using the copper particle catalyst electrode rich in dislocation defects prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0029] The methods used in the following examples are all conventional methods unless otherwise specified. The materials or reagents required in the following examples are all purchased from the market unless otherwise specified.
[0030] Example 1: Preparation of copper particle catalyst electrode containing abundant dislocation defects
[0031] (1) 758.6 mg Na2WO4·2H2O, 383 mg CuSO4, and 1921.9 mg urea were accurately weighed using an electronic balance and dissolved in 40 mL deionized water in sequence under ultrasonic conditions. The solution was then magnetically stirred at 900 rpm for 1 h.
[0032] (2) transferring the solution to a hydrothermal reactor, heating to 200° C. at a rate of 5° C. / min for 12 hours, washing the formed solid with deionized water and anhydrous ethanol to remove impurities, and placing the solid in a vacuum drying oven at 70° C. for 12 hours to obtain product A;
[0033] (3) Product A is placed in a muffle furnace, heated to 450°C at a rate of 5°C / min in an air atmosphere, and calcined for 12 hours to obtain CuWO4 powder;
[0034] (4) 20 mg of CuWO4 powder and 2 mg of carbon powder were dispersed in a mixture of 2 mL of ethanol, 0.5 mL of isopropanol, and 50 μL of Nafion by ultrasonication to obtain a uniform ink; under infrared lamp heating, the uniformly dispersed ink solution was coated on both sides of carbon paper (30 mm × 20 mm) as a working electrode;
[0035] (5) Using the working electrode of step (4), the Ag / AgCl electrode as the reference electrode, and the platinum electrode (30 mm × 30 mm) as the counter electrode, a three-electrode system was constructed, and 50 mM sodium sulfate solution was used as the electrolyte. A voltage of -1.3 V was applied for 30 min to remove WO4 2+ And Cu 2+ Reduction to Cu 0 , that is, a copper particle catalyst electrode containing rich dislocation defects is obtained.
[0036] The XRD pattern of the copper particle catalyst electrode containing abundant dislocation defects prepared in Example 1 is as follows: Figure 1 shown.
[0037] TEM of the copper particle catalyst electrode containing abundant dislocation defects prepared in Example 1 is as follows: Figure 2 As shown, it can be seen that the microscopic morphology of the catalyst is a nanoplate structure.
[0038] The reverse Fourier transform of the copper particle catalyst electrode containing rich dislocation defects prepared in Example 1 is as follows: Figure 3 As shown, it can be seen that there are a large number of edge dislocation defects in the catalyst.
[0039] Example 2: Effect of reducing nitrate to produce ammonia using a copper particle catalyst electrode rich in dislocation defects
[0040] (1) Preparation of electrolyte and nitrate pollutant stock solution
[0041] Use an electronic balance to accurately weigh 7.102 g of anhydrous sodium sulfate and dissolve it in 500 mL of deionized water. Transfer it to a 1 L volumetric flask and make up to volume with deionized water to obtain a 50 mM sodium sulfate solution. Use an electronic balance to accurately weigh 6.854 g of sodium nitrate and dissolve it in 500 mL of deionized water. Transfer it to a 1 L volumetric flask and make up to volume with deionized water to obtain a 5 g / L nitrate stock solution.
[0042] (2) Construction of the electrocatalytic nitrate reduction reactor, the specific steps are as follows:
[0043] a) The electrocatalytic reduction of nitrate ions was carried out using an H-type electrochemical reaction cell, which was divided into a cathode chamber and an anode chamber (volume of 150 mL), separated by a cation exchange membrane (Nafion-117). 100 mL of sodium sulfate electrolyte was added to the cathode and anode chambers respectively, and nitrogen was aerated for 10 min to remove dissolved oxygen. Then 2 mL of nitrate stock solution was added to the cathode chamber to make the nitrate nitrogen (NO3 - -N) with an initial concentration of 22.5 mg / L, and the solution was stirred with a magnetic stirrer for 10 min to mix evenly;
[0044] b) A three-electrode system was constructed using the copper particle catalyst electrode containing dislocation defects prepared in Example 1 as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum electrode (30 mm×30 mm) as a counter electrode.
[0045] (3) The operation of the electrocatalytic nitrate reduction reactor is as follows:
[0046] a) placing the entire electrochemical nitrate reduction reactor in a constant temperature water bath with a magnetic stirrer, wherein the reaction temperature is controlled at 25° C. and the magnetic stirring rate is controlled at 400 rpm during the entire reaction process;
[0047] b) Setting the electrochemical workstation parameters, using the chronoamperometry method for the electrocatalytic reduction of nitrate, setting the voltage to -1.1 V, and the reaction time to 240 min.
[0048] (4) Determine the electrocatalytic reduction reaction performance of nitrate, the steps are as follows:
[0049] a) At 0 min, 30 min, 60 min, 120 min, 180 min and 240 min of reaction, 2 mL of reaction solution was removed using a sampling needle;
[0050] b) Pipette 0.5 mL of sample solution into a colorimetric tube and dilute to 25 mL. Use an ultraviolet spectrophotometer (UV1000) to measure the target pollutant (NO3 - -N), the final product (NH3-N) and the intermediate product (NO2 - -N) concentration;
[0051] c) The removal rate of nitrate (η) is expressed as: η = (1-C t / C0)×100%;
[0052] The selectivity of ammonia nitrogen (S NH3 ) is expressed as: S NH3 =C NH3 / (C0-C t )×100%;
[0053] Among them, C t Indicates NO3 at time t - -N concentration (mg L -1 ), C0 represents NO3 - Initial concentration of -N (mg L -1 ),S NH3 represents the concentration of NH3-N at time t (mg L -1 ).
[0054] The copper particle catalyst rich in dislocation defects prepared in Example 1 was used as a working electrode, and an electrocatalytic nitrate reduction reaction was carried out according to the above steps.
[0055] Figure 4 The graph of nitrogen species concentration changing with time shows that during the electrocatalytic reduction of nitrate, NO3 - -N concentration decreased with time, and the removal rate reached 100% at 240 min; NH3-N concentration increased with time, and the selectivity reached 99.3% at 240 min; NO2 - The -N concentration showed a volcanic change over time and reached a peak of 5.4 mg L at 30 min. -1 , and only 0.1 mg L remained at 240 min. -1 , no obvious nitrous acid accumulation.
[0056] Figure 5 This is a continuous flow reaction stability test chart. There is no obvious attenuation in the reaction performance within 1440 minutes, which proves its stability.
[0057] The above experimental data prove that the copper particle catalyst electrode containing rich dislocation defects has high ammonia production activity and stability in the electrocatalytic reduction of nitrate.
[0058] (5) The effect of electrocatalytic reduction of nitrate under different conditions, the steps are as follows:
[0059] The working electrode was the copper particle catalyst electrode containing rich dislocation defects prepared in Example 1. The electrocatalytic reduction of nitrate was carried out according to the above steps. In addition, the voltage setting conditions were changed. The voltage was set to -0.9V, -1.0V, -1.1V, -1.2V and -1.3V for 5 reactions. The results are shown in Table 1. At 240min under all voltage ranges, NO 3- The removal rate of -N is 100%, the selectivity of NH3-N reaches the highest at -1.1V, and the Faraday current efficiency reaches the highest at -1.0V. Then, as the voltage continues to increase, the enhancement of the hydrogen evolution side reaction leads to a decrease in the current efficiency.
[0060] Table 1. Electrocatalytic reduction of NO3 by Cu-r at different voltages - -N removal rate, NH3-N selectivity and Faradaic efficiency
[0061] Voltage (V) -0.9 -1.0 -1.1 -1.2 -1.3 Removal rate (η) 100% 100% 100% 100% 100% <![CDATA[NH3-N Selectivity (S)]]> 21.8% 95.2% 99.4% 98.0% 98.7 Faradaic current efficiency (FE) 21.8% 98.6% 80.8% 40.4% 38.7%
[0062] The working electrode is the copper particle catalyst electrode containing rich dislocation defects prepared in Example 1, and the electrocatalytic reduction reaction of nitrate is carried out according to the above steps. - The initial concentration of -N was adjusted to 22.5mg / L, 45.0mg / L, 67.5mg / L and 90mg / L, and the reaction time was adjusted to 240min, 240min, 360min and 480min respectively. The results are shown in Table 2. It can be seen that the copper particle catalyst electrode with dislocation defects has a good reaction time for NO at four concentrations. 3- The removal rates of -N were all 100%, and the NH3-N selectivity was kept at a high level. The Faradaic current efficiency increased with the initial NO3 - -N concentration increases.
[0063] Table 2. Effects of different concentrations of NO 3- -N removal efficiency, NH3-N selectivity and Faraday current efficiency
[0064] <![CDATA[NO3 - -N concentration (mg / L)]]> 22.5 45 67.5 90 Removal efficiency (η) 100% 100% 100% 100% <![CDATA[NH3-N Selectivity (S)]]> 99.4% 97.0% 98.9% 99.7% Faradaic current efficiency (FE) 80.8% 85.9% 86.8% 87.1%
[0065] The working electrode was the copper particle catalyst electrode containing rich dislocation defects prepared in Example 1, and the continuous flow electrocatalytic reduction of nitrate was carried out for 1440 min according to the above steps. The results are shown in Table 3. 3- The removal efficiency of -N remained at 100% after 120 min, and the selectivity of NH3-N reached more than 97% after 240 min, indicating that the copper particle catalyst containing rich dislocation defects has high activity and stability in the electrocatalytic reduction of nitrate to ammonia.
[0066] Table 3. Continuous flow electrocatalytic reduction of nitrate NO 3- -N removal efficiency and NH3-N selectivity
[0067] Reaction time (min) 30 60 120 240 480 960 1200 1320 1440 Removal efficiency (η) 55.3% 90.8% 100% 100% 100% 100% 100% 100% 100% <![CDATA[NH3-N Selectivity (S)]]> 2.2% 27.8% 86.0% 98.8% 97.7 97.4% 97.3% 97.1% 97.2
[0068] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a copper particle catalyst electrode rich in dislocation defects, characterized in that: The steps include: (1) Dissolve tungstate, copper salt and urea in water and stir to mix; (2) placing the solution formed in step (1) into a hydrothermal kettle for hydrothermal reaction, and then washing and drying the solid powder obtained by the reaction; (3) calcining the solid powder obtained in step (2) in air to obtain CuWO4 powder; (4) loading the CuWO4 powder obtained in step (3) on an electrode substrate to prepare a working electrode; (5) electrochemically reducing the working electrode obtained in step (4) to obtain a copper particle catalyst electrode rich in dislocation defects.
2. The method for preparing a copper particle catalyst electrode rich in dislocation defects according to claim 1, characterized in that: In the step (1), the tungstate is one or more of Na2WO4·2H2O and K2WO4·2H2O; the copper salt is one or more of CuCl2, CuSO4 and Cu(NO3)2.
3. The method for preparing a copper particle catalyst electrode rich in dislocation defects according to claim 1, characterized in that: In the step (1), the molar ratio of tungstate, copper salt and urea is 1:1.05:10-20.
4. The method for preparing a copper particle catalyst electrode rich in dislocation defects according to claim 1, characterized in that: In the step (2), the hydrothermal reaction temperature is 160° C. to 200° C., and the reaction time is 8 to 16 hours.
5. The method for preparing a copper particle catalyst electrode rich in dislocation defects according to claim 1, characterized in that: In the step (3), the calcination temperature is 300° C. to 500° C., and the calcination time is 2 to 12 hours.
6. The method for preparing a copper particle catalyst electrode rich in dislocation defects according to claim 1, characterized in that: In the step (5), the voltage of the electrochemical reduction is -1.3V to -1.5V, the reference electrode is an Ag / AgCl electrode, and the counter electrode is a Pt electrode.
7. A copper particle catalyst electrode rich in dislocation defects, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the copper particle catalyst electrode rich in dislocation defects as claimed in claim 7 in the electrocatalytic reduction of nitrate.
9. The use according to claim 8, characterized in that: The reaction voltage of the electrocatalytic reduction of nitrate is -1.0 to -1.1V.
Citation Information
Cited By
Preparation method and application of oxygen vacancy-rich monatomic transition metal catalyst M1 / CeO2
CN118513042A